Across empires taking U.S. history into transimperial terrain - Hoganson, Kristin L.; Sexton, Jay 1978- (Duke University Press, 2019)
In pursuit of profit -- Fur sealing and unsettled sovereignties / John Soluri -- Crossing the Rift: American steel and colonial labor in Britain's East Africa protectorate / Stephen Tuffnell -- Transimperial politics 'our indian empire': the transimperial origins of U.S. liberal imperialism / Michel Gobat -- Empire, democracy, and discipline: the transimperial history of the secret ballot / Julian Go -- Medicine to drug: opium's transimperial journey / Anne L. Foster -- Governing structures -- One service, three systems, many empires: the U.S. Consular Service and the growth of U.S. global power, 1789-1924 / Nicole M. Phelps -- Transimperial roots of American anti-imperialism: the Transatlantic radicalism of free trade, 1846-1920 / Marc-William Palen -- The permeable South: imperial interactivities in the Islamic Philippines, 1899-1930s / Oliver Charbonneau -- Living transimperially -- Liberian colonization and African American migration across Anglophone settler colonial empires / Ikuko Asaka -- Entangled in empires: British Antillean migrations in the world of the Panama Canal / Julie Greene -- World War II and the promise of normalcy: overlapping empires and everyday life in the Philippines / Genevieve Clutario -- Resistance across empires -- Fighting John Bull and uncle Sam: South Asian revolutionaries confront the modern state / Moon-Ho Jung -- Indigenous child removal and transimperial indigenous women's activism across settler colonial nations in the late twentieth century / Margaret D. Jacobs
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte; Transnationalism; Cosmopolitanism / United States; Transnationalism / Political aspects / United States; International relations; Internationale Politik; Transnationale Politik; USA; Aufsatzsammlung